Effect of FeCl3 in NaCl-MgCl2 molten salts on the corrosion behavior of 316 stainless steel at 600 °C. (March 2023) - Lu, Pengfei; Liu, Qi; Bao, Hongliang; Pan, T.J.; Tang, Zhongfeng
Abstract: The effect of FeCl3 addition on the corrosion of 316 stainless steel (316SS) in NaCl-MgCl2 salts at 600 °C was studied through a static corrosion test. FeCl3 added into NaCl-MgCl2 salt reacted with Fe in 316SS and accelerated the corrosion of 316SS. After corrosion, Fe 2+ and Fe 3+ coexisted in the NaCl-MgCl2 salt, and the concentration of Fe 2+ was higher than that of Fe 3+ . With the increased FeCl3 concentration in NaCl-MgCl2 salt, the grain boundary corrosion of 316SS was aggravated, and the concentration difference of Fe 2+ and Fe 3+ in the salt increased after corrosion. Highlights: The effect of Fe 3+ in NaCl-MgCl2 on corrosion behavior of 316SS was firstly studied. XANES results confirmed that Fe 3+ in salts could converted to Fe 2+ after corrosion. Grain boundary corrosion of 316SS was aggravated with increased FeCl3 concentration.